2009
DOI: 10.1186/1749-799x-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross exercise on quadriceps acceleration reaction time and subjective scores (Lysholm questionnaire) following anterior cruciate ligament reconstruction

Abstract: BackgroundAnterior cruciate ligament (ACL) injury or reconstruction can cause knee impairments and disability. Knee impairments are related to quadriceps performance – accelerated reaction time (ART) – and disability to performance of daily living activities which is assessed by questionnaires such as the Lysholm knee score. The purposes of this study were to investigate the effect of cross exercise, as supplementary rehabilitation to the early phase of ACL reconstruction: a) on quadriceps ART at the angles 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…The results confirm previous findings that quadriceps improvements were greater for ACL-reconstructed patients who followed 3 days per week CEE rather than the control one. 40,41 However, in our study no statistical results were found between the two experimental groups. From rehabilitation perspective this would appear logical that a supplementary exercise program attached to the classic rehabilitation program is more effective and is more likely to minimize QD, compared with a rehabilitation one performed alone.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The results confirm previous findings that quadriceps improvements were greater for ACL-reconstructed patients who followed 3 days per week CEE rather than the control one. 40,41 However, in our study no statistical results were found between the two experimental groups. From rehabilitation perspective this would appear logical that a supplementary exercise program attached to the classic rehabilitation program is more effective and is more likely to minimize QD, compared with a rehabilitation one performed alone.…”
Section: Discussioncontrasting
confidence: 60%
“…It has been reported that CEE improves quadriceps muscle strength at 45-and 90-degree knee angles and quadriceps accelerated reaction time at 90 degrees of knee flexion on the ACL-reconstructed knee in the early rehabilitation stage; 8 weeks following the reconstruction. 40,41 Arai et al 42 investigated, in six orthopedic patients, the effect of CE on QS by applying a proprioceptive neuromuscular facilitation (PNF) exercise, at various knee angles. The PNF-CE was significantly effective on QS at 60 degrees of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within Greece, there is a gap in the literature regarding self-reported questionnaires to evaluate functional status of osteoarthritis (OA) patients, or patients' progress pre-operatively and post-operatively. Lysholm [16] and KOS-ADL [17] previously adapted in Greek traditionally assess more acute knee injury cases. Therefore, KOOS was thought as an appropriate questionnaire for assessing more active patients undergoing TKR compared to WOMAC [11].…”
Section: Introductionmentioning
confidence: 99%
“…The obtaining full ROM, especially hyperextension and acceptable quadriceps muscle strength before surgery, determine surgical timing and are primary goals of early postoperative rehabilitation [7,19]. Knee impairments and disability to perform activities of daily living following ACL injury or reconstruction may be assessed by the Lysholm knee score [20].…”
Section: Introductionmentioning
confidence: 99%